Effect of drug induced sleep endoscopy on intraoperative decision making in pediatric sleep surgery. (March 2020) - Dmowska, Julia; Larson, Stephen Reed; Gillespie, M. Boyd; Sheyn, Anthony
Abstract: Objectives: To demonstrate the effect of drug induced sleep endoscopy (DISE) on intra-operative decision making during pediatric sleep surgery for obstructive sleep apnea (OSA). Methods: A retrospective chart review was performed on pediatric (3–17 years) patients with moderate-to-severe OSA (7.2–71.8) who underwent drug induced sleep endoscopy at the time of initial sleep surgery. The characteristics evaluated included age, race, gender, site of obstruction, type of surgical intervention, pre- and post-operative apnea and hypopnea index. Of the 26 patients that were identified, 18 had both a pre- and post-operative polysomnograms result. Results: All patients underwent DISE immediately prior to surgical treatment. The mean pre-operative AHI for the 18 patients with post-operative polysomnogram results was 21.3 (7.2–71.8). The mean post-operative AHI for the 18 patients was 7.6 (0.7–25.1). There was a significant difference between pre- and post-operative AHI (p < 0.001). Of the 26 patients, the most common area of collapse was the soft palate, occurring in 17/26 (65.4%) patients. Base of tongue involvement was found to be present in 11/26 (42.3%) patients, and the epiglottis was involved in 4/26 (15.4%). Evidence of multilevel collapse was observed in 6/26 (23.1%) patients. Patients observed to have palatal collapse underwent a pharyngoplasty (20/26; 76.9%) at the time of adenotonsillectomy. Three (11.5%) patients underwent a tongue reduction. Conclusion: This study provides additional evidence that DISE can affect intra-operative decision making, with the potential for improved post-operative outcomes. A randomized controlled study is needed to determine if these outcomes are better than what can be achieved without DISE.